1968
DOI: 10.1111/j.1471-4159.1968.tb11633.x
|View full text |Cite
|
Sign up to set email alerts
|

Developmental Changes in Mouse Brain: Weight, Water Content and Free Amino Acids

Abstract: Abstract— —Glutamic acid, glutamine, GABA and aspartic acid exhibited postnatal increases in the developing mouse brain at the same time that the other amino acids, both essential and non‐essential, of the pool decreased. The most significant decreases were observed in the concentrations of taurine, phosphoethanolamine, glycine and alanine. The period of rapid accumulation of the members of the glutamic acid family in the mouse brain was concurrent with dramatic increases and decreases in brain weight and wate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
40
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(47 citation statements)
references
References 2 publications
7
40
0
Order By: Relevance
“…3C. The brain weights of our control mice (La F/Ϫ ) basically agreed with results from previous studies (46). The brain mass plot revealed that consistent with the temporal activity of Cre CaMKII , a difference in brain mass first appeared to distinguish La-deleted and control mice after 5 weeks.…”
Section: Resultssupporting
confidence: 79%
See 1 more Smart Citation
“…3C. The brain weights of our control mice (La F/Ϫ ) basically agreed with results from previous studies (46). The brain mass plot revealed that consistent with the temporal activity of Cre CaMKII , a difference in brain mass first appeared to distinguish La-deleted and control mice after 5 weeks.…”
Section: Resultssupporting
confidence: 79%
“…The brain mass plot revealed that consistent with the temporal activity of Cre CaMKII , a difference in brain mass first appeared to distinguish La-deleted and control mice after 5 weeks. Remarkably, for several weeks thereafter, a time when the normal developing mouse brain transitions from a state of growth to a more constant steady-state level (46) (Fig. 3C, gray line), the La…”
Section: Resultsmentioning
confidence: 99%
“…Given that AQP4 allows bidirectional water transport (6), a second question is whether the endfoot pool of AQP4 plays a role in the resorption of brain water that occurs postnatally (19). Notably, the extracellular volume fraction is highest in the newborn and diminishes with age (20).…”
Section: Discussionmentioning
confidence: 99%
“…After desiccation, water content was calculated from the wet-dry weight difference. For younger animals, water content measurements were available from previous reports (Agrawal et al, 1968;Cohadon and Desbordes, 1986;Kulak et al, 2010;Larvaron et al, 2006).…”
Section: Water Contentmentioning
confidence: 99%
“…At the age of 6 and 12 months, water content was 79 AE 1% (n ¼ 4) and 79 AE 1% (n ¼ 6), respectively, and reduced to 75 AE 1% at the age of 24 months (n ¼ 9, p < 0.01 vs. 6 and 12 months). Average reported water content at the age of 1 month was 80 AE 1% (Agrawal et al, 1968;Cohadon and Desbordes, 1986;Kulak et al, 2010;Larvaron et al, 2006). Water content at these ages and interpolated at the age of 3 and 18 months was used to estimate absolute concentration of metabolites in the brain.…”
Section: Quantification Of Neurochemicalsmentioning
confidence: 99%